Highly Elevated Prevalence of Spinobulbar Muscular Atrophy in Indigenous Communities in Canada Due to a Founder Effect. (August 2021) - Leckie, Jamie N.; Joel, Matthew M.; Martens, Kristina; King, Alexandra; King, Malcolm; Korngut, Lawrence W.; de Koning, A.P. Jason; Pfeffer, Gerald; Schellenberg, Kerri L.
Abstract : Objective: Spinobulbar muscular atrophy (SBMA) is an X-linked adult-onset neuromuscular disorder that causes progressive weakness and androgen insensitivity in hemizygous males. This condition is reported to be extremely rare, but has higher prevalence in certain populations due to multiple founder effects. Anecdotal observations of a higher prevalence of SBMA in patients of Indigenous descent in Saskatchewan led us to perform this study, to estimate the disease prevalence, and to attempt to identify a founder effect. Methods: For our prevalence estimation, we identified patients with confirmed SBMA diagnosis from the Saskatoon neuromuscular clinic database for comparison with population data available from Statistics Canada. For our haplotype analysis, participants with SBMA were recruited from 2 neuromuscular clinics, as well as 5 control participants. Clinical data were collected, as well as a DNA sample using saliva kits. We performed targeted quantification of DXS1194, DXS1111, DXS135, and DXS1125 microsatellite repeats and the AR GGC repeat to attempt to identify a disease haplotype and compare it with prior studies. Results: We estimate the prevalence of SBMA among persons of Indigenous descent in Saskatchewan as 14.7 per 100, 000 population. Although we believe that this is an underestimate, this still appears to be the highest population prevalence for SBMA in the world. A total of 21 participants were recruited for the haplotype study, and we identified a unique haplotype that was shared among 13 participants with Indigenous ancestry. A second shared haplotype was identified in 2 participants, which may represent a second founder haplotype, but this would need to be confirmed with future studies. Conclusions: We describe a very high prevalence of SBMA in western Canadians of Indigenous descent, which appears to predominantly be due to a founder effect. This necessitates further studies of SBMA in these populations to comprehensively ascertain the disease prevalence and allow appropriate allocation of resources to support individuals living with this chronic disease.